Hubungan Dukungan Keluarga dengan Kelengkapan Imunisasi Tt pada Ibu Hamil di Wilayah Kerja Puskesmas Madello Kota Barru Tahun 2022 - Rasmawati; Nur Fadhilah (Universitas Muhamadiyah Manado, 2022)
TT ​​immunization is the provision of immunity through TT absorbent vaccine containing purified tetanus toxoid to provide active immunity against tetanus.. Objective : To determine the relationship between Age, Knowledge, Family Support with completeness of TT immunization for pregnant women in the working area of ​​Madello Public Health Center, Barru City in 2022. Methods : This study uses cross sectional method. The population in this study were all pregnant women who visited the Puskesmas. The sampling technique is purposive sampling. Data was processed using SPSS and analyzed by univariate and bivariate with chi-square statistical test and presented in the form of a frequency distribution table. The results of the study: Shows that there is is a relationship between family support and completeness of immunization where the p value = 0.01, this means that the p value < (0.05) because the p value is less than 0.05. Conclusion: There is a relationship between Age, Knowledge, and Family Support with the completeness of TT immunization in the working area of ​​the Madello Health Center, Barru City in 2022.